Effect of STEM Problem-Based Learning on Achievement in Basic Science among Secondary School Students - Dr VINCENT CHUKWUJEKWU DAVIDSON; Theresa Obiageli Maduegbunam; Dr Juliana Anayo Odo; Dr Ignatius Ifeanyi Adonu; Chidi Nathaniel Agbo (International Journal of Research in STEM Education)
This study was carried out to examine the effect of STEM Problem Based Learning on students’ achievement in Basic Science. This is in consideration of the fact that the Nigerian National Policy on Education provides that for a student to study any of the core science subjects at the Senior secondary school level, he must have to score a credit pass in Basic Science at Junior Secondary School level. Without a credit pass in any of the science subjects that make up Basic Science (Biology, Chemistry and Physics), a student cannot study any of the course in science, technology, engineering or mathematics at the tertiary education level. Unfortunately, literatures show that there is massive failure of students in Basic Science especially at the Basic      Education Certificate Examination. This study is guided by three research questions and three research hypotheses. The population for this study is junior secondary school form 2 students of Nsukka local government area of Enugu State in Nigeria. The study used random sampling technique to sample schools and employed pre-experimental research design. The sample was sub-divided into two: low ability learners and high ability learners. Data was collected at two different periods (pretest and post-test) using an achievement test constructed by the researchers. The analysis was carried out using ANCOVA, Independent Sample T-test and Paired Sample T-test using IBM SPSS version 23. The results of the analysis showed that STEM PBL is a good strategy that can be used to increase students’ achievement in Basic Science.